Selected Lectures of the Course “Take care of children”, 2nd Edition, Virtual Edition; Cagliari (Italy); October 31st, 2020 - Various Authors, --- (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2020)
Selected Lectures of the Course “Take care of children”, 2nd Edition • Virtual Edition • PRENDERSI CURA DEI BAMBINI CON LA FITOTERAPIA E GLI INTEGRATORI ALIMENTARI • ISTRUZIONE PER L’USO, OPPORTUNITÀ E LIMITI • Cagliari (Italy) • October 31st, 2020 LECT 1 • Food supplements in pediatric daily clinical practice [Gli integratori alimentari nella pratica clinica quotidiana in età pediatrica] • D. Careddu (Novara, Italy) LECT 2 • Dangerous relationship between junk food, microbiota and neurodevelopment [Relazioni pericolose tra junk food, microbiota e neurosviluppo] • E. Lombardi Mistura (Bergamo, Italy) LECT 3 • How to read the label of a botanical food supplement [Come leggere l’etichetta di un integratore alimentare] • M. Biagi (Siena, Italy) LECT 4 • Plants extracts active on the immune system from immune modulation to allergies [Piante ed estratti vegetali attivi sul sistema immunitario dall’immunomodulazione alle allergie] • O. Al Jamal (Cagliari, Italy) LECT 5 • Probiotics: an update [Novità in tema di probiotici] • S.A. Nervi (Milan, Italy) LECT 6 • Children and teenager’s stress: adaptogens rule [Gli adattogeni e lo stress psicofisico dal bambino all’adolescente] • G. Trapani (Sanremo, Italy)